THE RE-DOCUMENTATION OF JEPARA’S CARVING MOTIFS: AN EARLY STUDY - Iswahyudi Iswahyudi (Journal of Social Studies (JSS), 2017)
This study aim to describe the development of carved art motifs in Jepara. The target population of artworks carving is some distribution of works that represent the period, so that the selection of data sources is also tight and considered representative. In this study it is required to produce a qualitative descriptive development study so that it approaches synchronic diachronik. The research step is done through the stages of observation, interviewing, making documentation, comparing historical information and see some works that have never been used by other researchers. The results: (1) Associated with the motive of the Queen of Sima money is considered the earliest is estimated in the VII century by physical evidence has not been found but on the myth is still attached to society carver Jepara. (2) The motifs that are representative of the era is Kalinyamat motif is believed to have existed at the beginning of the XVI century is still intact until now in the Mantingan Mosque Jepara. (3) Some artworks carved R.A. Kartini called Kartini motif by approach with her family can be presented in this research. (4) Various discoveries of masterpiece maestro Jepara artists can still be saved and are in Jepara carving museum. Followed by various colonial works both in the museum and in the home entrepreneur meubelair called the pre booming motif. (5) Contemporary sculpture art works can be found in groups called booming and post booming motifs that mostly reside and are displayed in some show rooms center meubelair Jepara city.Keywords: Jepara, development, carving motifs